2022
DOI: 10.1126/science.abf5546
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of human interneuron progenitors promotes brain tumors and neurological defects

Abstract: Evolutionary development of the human brain is characterized by the expansion of various brain regions. Here, we show that developmental processes specific to humans are responsible for malformations of cortical development (MCDs), which result in developmental delay and epilepsy in children. We generated a human cerebral organoid model for tuberous sclerosis complex (TSC) and identified a specific neural stem cell type, caudal late interneuron progenitor (CLIP) cells. In TSC, CLIP cells over-proliferate, gene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 59 publications
0
72
0
Order By: Relevance
“…We reanalyzed recent, landmark single cell transcriptomics studies and performed new experiments (Bhaduri et al, 2020; Eichmüller et al, 2022; Kanton et al, 2019; Khan et al, 2020; Velasco et al, 2019) ( Fig 1A ) to answer 3 questions: What stress pathways are active in organoids? Does stress occur in all or only certain organoid protocols?…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We reanalyzed recent, landmark single cell transcriptomics studies and performed new experiments (Bhaduri et al, 2020; Eichmüller et al, 2022; Kanton et al, 2019; Khan et al, 2020; Velasco et al, 2019) ( Fig 1A ) to answer 3 questions: What stress pathways are active in organoids? Does stress occur in all or only certain organoid protocols?…”
Section: Resultsmentioning
confidence: 99%
“…Besides a lack of cell type specification, incomplete maturation due to stress was previously suggested (Bhaduri et al, 2020). As a positive control for maturation, we took two media conditions that affected maturation (Eichmüller et al, 2022). We grew pairwise matched samples in two different media conditions, then analyzed together ( Fig 4G ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on this, the change in EDNRB expression may have promoted human brain expansion by increasing the proliferation of the subpopulation of radial glia that express EDNRB . In addition, a recent study identified a population of caudal late interneuron progenitor (CLIP) cells marked by expression of EDNRB and PTGDS along with caudal ganglionic eminence markers (Eichmüller et al 2022). As both EDNRB and PTGDS have strongly human-biased ASE it would be interesting to investigate if this population of cells exists in chimpanzee brain organoids and if it may have expanded in humans.…”
Section: Resultsmentioning
confidence: 99%